HUBUNGAN PERAN KELUARGA DENGAN KUALITAS HIDUP PADA LANSIA DI RW I KELURAHAN ASAM KUMBANG MEDAN - Dina Eudia Meha; Lenny Lusia Simatupang (Jurnal Riset Multidisiplin Edukasi, 2025)
Background : The family has an important role in maintaining and improving the quality of life of the elderly. They can change the behavior of the elderly towards clean and healthy living habits, improve the environment, and provide health services. Good quality health can slow down the physical decline of the elderly. The important role of the family in maintaining  the  quality  of  life  of  the  elderly  includes  creating  good  relationships, providing a feeling of security and comfort, listening to and meeting the needs of the elderly, as well as motivating and involving them in decision making. Family support also plays an important role in increasing the self-confidence of the elderly. Families can involve the elderly in making decisions and solving problems together, providing freedom in physical and mental changes, as well as providing space and time. Objective : to see the relationship between family roles and the quality of life of the elderly at RW I kelurahan asam kumbang. Method: This study used a quantitative research method of cross sectional approach. The sampling technique researchers use in determining their respondents is the total sampling technique. The data analysis technique used is the korelasi pearson test. Result: The result of the study show that there is a relationship between family roles and the quality of life of the elderly at RW I kelurahan asam kumbang. The korelasi pearson test show a p-value of 0,04 (<0,05) Conclusion: There is a relationship between family roles and the quality of life of the elderly at RW I kelurahan asam kumbang.